ANALISIS RISIKO SISTEM INFORMASI PENJUALAN BERBASIS ISO 31000 - RISK MANAGEMENT DI PT. REMAJA ROSDAKARYA - Tri Ramdhany; Rio Andriyat Krisdiawan (Universitas Kuningan, 2018)
ABSTRACT PT. Adolescent Rosdakarya is a book publishing company in Indonesia with two strategic business units namely publisher and printing. In conducting business activities of PT. Adolescent Rosdakarya has implemented an information system on the sales of sales information systems that can generate various information that can be useful to support sales activities. This makes the activities that occur in it becomes very crucial. Running elements and system components well becomes very important to support the performance of the system itself. It can not be denied, however, that the possibility of various threats and risks may inhibit and even paralyze activity within the system. Current risk management has become the main reference in the application of various management system standards, which will in particular refer to the existing provisions of ISO 31000 Risk Management- Principles and guidelines. From the result of risk analysis based on ISO 31000 - Risk Management that used as risk management standard in research got risk priority value based on measurement process which have been done at each risk which have been identified and analyzed before. So that the company can do prevention, handling and improvement for the future in accordance with the level of priority risk. Keywords: Risk Management. ISO 31000. Sales Information System